2018
DOI: 10.1002/mrm.27155
|View full text |Cite
|
Sign up to set email alerts
|

PRO‐QUEST: a rapid assessment method based on progressive saturation for quantifying exchange rates using saturation times in CEST

Abstract: Because of the reduced scan time and insensitivity to nonchemical exchange factors such as direct water saturation, PRO-QUEST can serve as an excellent alternative for researchers and clinicians interested to map pH changes in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…[28][29][30][31] Ideally, for providing the most useful estimation of the metabolite of interest, the actual physical CEST propertiesproton exchange rate, and solute concentration should be mapped. In accordance, various efforts were previously taken to achieve quantitative CEST imaging 32 such as the quantitation of exchange using saturation power (QUESP) or time (QUEST) [33][34][35] and Omega plot 36 methods. These methods exploit the dependency of the CEST signal on the saturation power (or saturation time) and fit the MTR asym for a single offset as a function of the saturation parameter to estimate the labile proton volume fraction and exchange rate.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] Ideally, for providing the most useful estimation of the metabolite of interest, the actual physical CEST propertiesproton exchange rate, and solute concentration should be mapped. In accordance, various efforts were previously taken to achieve quantitative CEST imaging 32 such as the quantitation of exchange using saturation power (QUESP) or time (QUEST) [33][34][35] and Omega plot 36 methods. These methods exploit the dependency of the CEST signal on the saturation power (or saturation time) and fit the MTR asym for a single offset as a function of the saturation parameter to estimate the labile proton volume fraction and exchange rate.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the PRO-QUEST method with single irradiation frequency might be susceptible to B0 shifts. As the previous pre-clinical study reported, this could be mitigated by using broad bandwidth saturation pulses (21). A bandwidth of 300 Hz was used in the present study in consideration of the B0 effect.…”
Section: Discussionmentioning
confidence: 99%
“…The PRO-QUEST sequence was originally developed on a 9.4T pre-clinical scanner to reduce the time for measuring chemical exchange rates (21). In this method, an initial saturation pulse sequence is followed by delays ( Figure 1A) or off-resonance saturation pulses ( Figure 1B) interleaved under non-steady-state conditions while the water magnetization is sampled subsequently through a Look-Locker acquisition until a steady-state magnetization is reached.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations